Directly anterior approach for total hip arthroplasty with an acetabular structural bone graft for developmental dysplasia of the hip (Crowe III and IV): a concise 5-year follow-up evaluation - Lijia Pei; Ben Liu; Yifan Wu; Yuanhang Wang; Wenhao Sun; Wenju Chang; Xinshe Zhou (BMC Musculoskeletal Disorders)
Abstract Background This study evaluated the results of total hip arthroplasty (THA) via the direct anterior approach (DAA) in the lateral decubitus position combined with acetabular reconstruction via a bulk autograft for patients with developmental dysplasia of the hip (Crowe III and IV). Patients and methods A retrospective study was conducted to analyse 16 patients (16 hips) with Crowe type III and IV developmental dysplasia of the hip (DDH) who underwent THA from June 2016 to July 2021. We recorded and analysed variables such as age, sex, height, body mass index (BMI), length of surgical incision, duration of surgery, intraoperative blood loss, Harris hip score, visual analogue scale (VAS) score, lower limb length, and pelvic radiograph analysis. Results The mean age of the patients was 59.3 years, the mean BMI was 22.8 kg/m2, and the Crowe classification was type III in 13 hips and type IV in 3 hips. Sixteen patients were followed up with a mean follow-up time of 56.6 (32–92) months. The Harris hip score increased from 48.6 ± 7.5 points preoperatively to 89.6 ± 4.4 points at the final follow-up (t = -18.8, P < 0.001).The VAS score for activity decreased from 7.3 ± 0.8 points preoperatively to 1.0 ± 0.7 points at the final follow-up, which was a statistically significant difference compared with the preoperative score (t = 22.2, P < 0.001). The difference in the length of both lower limbs decreased from 3.0 ± 0.7 cm preoperatively to 0.9 ± 0.4 cm at the final follow-up, and the difference was statistically significant compared with the preoperative difference (t = 10.8, P < 0.001). The acetabular cup coverage was satisfactory. Conclusions Acetabular structural bone grafting THA with lateral decubitus DAA was used to treat Crowe type III and IV DDH with satisfactory efficacy in the medium term, but the learning curve was long. Surgeons need to have extensive clinical experience with DAA to THA.